Narrative inquiry of translators’ identities: A study of meaning-making in narrating knowledge - Geng, Qiang (Frontiers in Psychology, 2023)
Translators have generated retrospective accounts of their working experience, which contribute to an expansive corpus of knowledge on translation. A plethora of research has explored how this knowledge could enrich our perception of varied questions concerning translation process, strategies, norms, and other social and political respects within conflictual settings in which translation has engaged. In contrast, few attempts have been made to gain a translator-centered understanding of what this knowledge could mean for its narrators. In line with narrative inquiry, this article proposes a human-centered approach to translator’s knowledge narrating and a shift from positivistic to post-positivistic investigation into specific questions about how translators make sense of who they are as well as the meaning of their lives by structuring their experiences into a sequential and meaningful narrative. The general question is what strategies are employed to construct what types of identities. A holistic and structured analysis of five narratives by senior Chinese translators involves macro and micro dimensions. With a view to methods employed by scholars in different fields, the study identifies four types of narratives, namely, personal, public, conceptual/disciplinary, and metanarrative, which are used throughout our cases. Micro-analysis of narrative structure demonstrates that life events are often arranged in a chronological sequence, among which critical events are favored to indicate a turning point or crisis for transformation. Storytellers tend to adopt strategies of personalizing, exemplifying, polarizing, and evaluating to construct their identities and what translation experience means to them. This article concludes that apart from communicating translation knowledge, translators make sense of what translation experience means to them as a professional translator and more importantly as a real person living through social–cultural–political vicissitudes, thus contributing to a more translator-centered vision of translation knowledge.